ASPEK MORAL DAN NILAI-NILAI SOSIAL DALAM LIRIK-LIRIK LAGU REGGAE YANG DINYANYIKAN OLEH DEN BASITO: ASPEK MORAL DAN NILAI-NILAI SOSIAL DALAM LIRIK-LIRIK LAGU REGGAE YANG DINYANYIKAN OLEH DEN BASITO - Erni Fatmawati; M. Shoim Anwar (Universitas PGRI Adi Buana Surabaya, 2015)
The aspects of moral and social values are also many contained in any reggae song lyrics. Reggae song lyrics have a message about the behaviors of society and always uphold high human values. Because breath laden reggae lyrics that contain the struggle and the liberation of the weak from the authorities. Reggae music, the appellation of the rastaman, has become a new form of subculture in this country, where the young people determine and classifies themselves. Just how social observers and the members of the community to understand with the culture that they choose in order to avoid misrepresentation harmful to them. Data used in the study is the aspect of moral and social values. The sources of data are from the lyrics of the song sung by Den reggae Basito, books, internet, and Rastafaria group. Data collection technique in this study is transcription technique transform of oral into written data. While the methods used to analyze the data in this research is descriptive qualitative method. Based on the result of analysis the lyrics song sung by den Basito, in this study explained that every reggae song sung by Den Basito also has the meaning contained. In any lyrics, Den Basito tries to convey moral and social values in society today. Political world also become inspiration of making the lyric song. Den Basito wants to convey the natural beauty that we have if we respect for each other. In the lyrics, contain many meanings such as loyalty, religion, morality, politics, knowledge, beauty, and social value.